2004
DOI: 10.1262/jrd.50.579
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Culture of Mouse Preantral Follicles Using Membrane Inserts and Developmental Competence of In Vitro Ovulated Oocytes

Abstract: Abstract. To develop a reliable follicle culture system, mouse preantral follicles 150-200 µm in diameter were cultured individually for 5 or 6 days in membrane inserts or in droplets, and then induced to ovulate with hCG (Experiment 1). The nuclear maturation and developmental competence of the oocytes that ovulated from the follicles cultured in inserts were determined (Experiment 2). There was no significant difference between the two culture systems in the survival rate (83 and 77%). However, follicles cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The polyester membranes, transfixed to the transwell inserts, are available in 3 pore sizes; 0.4 µm, 0.8 µm and 3 µm. Transwell inserts have been used for in vitro culture and maturation of ovarian follicles [24][25][26]. The polyester membrane is fixed to the bottom of the insert, onto which ovarian follicles are cultured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyester membranes, transfixed to the transwell inserts, are available in 3 pore sizes; 0.4 µm, 0.8 µm and 3 µm. Transwell inserts have been used for in vitro culture and maturation of ovarian follicles [24][25][26]. The polyester membrane is fixed to the bottom of the insert, onto which ovarian follicles are cultured.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the polyester membrane in the transwell insert is translucent, allowing excellent cell visualization under phase contrast microscopy without the need for staining. The transwell insert with polyester membrane is a well documented system for in vitro culture and maturation of ovarian follicles [24][25][26]. The major limitation with this technique is that the original three-dimensional structure of the ovarian follicles is lost by attachment to the transwell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In this culture system, we used supplementation of follicular fluid in a fixed presentation (5%) rather than hypoxanthine. Down et al 9 reported that hypoxanthine in follicular fluid has been identified as one such meiosis arresting substance.…”
Section: Oocyte Growth and Quality After Ivgmentioning
confidence: 99%
“…There is quite a variation in the oocyte calcium intensity. 9 Results reported from IVG culture systems from different species of the mammalian oocyte 1,10 , from 1989 to 2015 show a different potential of different species including mouse, pig, and cow with matrix collagen, resulting in a positive result for IVM or IFV methods and obtaining offspring. In domestic species, the first successful IVG culture system that supports the growth of oocytes from mid-growth phase in preantral (late secondary) follicles to the final size was reported by Hirao et al 11 (Table 3).…”
Section: Oocyte Growth and Quality After Ivgmentioning
confidence: 99%
“…In view of clinical and agricultural interests, efforts have been made to develop culture systems using primordial follicles, because the follicles at this stage potentially represent a large source of oocytes in humans and large mammals (Eppig and O'Brien, 1996;Abir et al, 1999;Abir et al, 2001;Demeestere et al, 2002). While in vitro experimental systems suitable for studying follicular growth are available, only a handful of reports describing in vitro ovulation models in mammals have been published (Baranczuk and Fainstat, 1976;Brännström et al, 1987;Rose et al, 1999;Adam et al, 2004). This is probably due to the difficulty of setting stable conditions to obtain reproducible results.…”
Section: Introductionmentioning
confidence: 99%